Effective ways and techniques of teaching a foreign language - Mustafaeva Guzal Avasxonovna (Zien Journals, 2022)
This article covers the various methods and forms of work in which educational methods are used in the implementation of tasks that must be performed in order to achieve the goals pursued by a particular pedagogical process.In this regard, the methods of teaching foreign languages are considered.
Keywords: method; Express-method; traditional problematic approach intensive; grammatic